1993
DOI: 10.1091/mbc.4.8.803
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and genetic analyses of the Caenorhabditis elegans dpy-2 and dpy-10 collagen genes: a variety of molecular alterations affect organismal morphology.

Abstract: We have identified and cloned the Caenorhabditis elegans dpy-2 and dpy-10 genes and determined that they encode collagens. Genetic data suggested that these genes are important in morphogenesis and possibly other developmental events. These data include the morphologic phenotypes exhibited by mutants, unusual genetic interactions with the sqt-1 collagen gene, and suppression of mutations in the glp-1 and mup-i genes. The proximity of the dpy-2 and dpy-10 genes (3.5 kilobase) and the structural similarity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 59 publications
2
72
0
Order By: Relevance
“…In addition, 33 mutations in seven different cuticle collagen genes of C. elegans have been reported (Johnstone et al, 1992;Kramer, 1993;Kramer and Johnson, 1993;Levy et al, 1993; this paper), as well as 20 mutations in the two basement membrane collagen genes (Guo et al, 1991;Kramer, 1993). In the cuticle mutants, most of which were isolated after EMS treatment, glycine is replaced by either aspartic acid, glutamic acid, or arginine.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, 33 mutations in seven different cuticle collagen genes of C. elegans have been reported (Johnstone et al, 1992;Kramer, 1993;Kramer and Johnson, 1993;Levy et al, 1993; this paper), as well as 20 mutations in the two basement membrane collagen genes (Guo et al, 1991;Kramer, 1993). In the cuticle mutants, most of which were isolated after EMS treatment, glycine is replaced by either aspartic acid, glutamic acid, or arginine.…”
Section: Discussionmentioning
confidence: 82%
“…Likewise, limited secretion of SQT-3 was detected in dpy-17(e164) animals raised at 15°(data not shown). To confirm that intracellular retention of SQT-3 is specific to dpy-17(0) mutants, we tested SQT-3 immunolocalization in dpy-7(e88), dpy-10(e128), and dpy-13(e184) cuticle collagen mutants (von Mende et al 1988;Johnstone et al 1992;Levy et al 1993). In all cases, SQT-3 is secreted and assembles in the cuticle normally at 20° (Figure 9).…”
Section: Resultsmentioning
confidence: 95%
“…A spontaneous mutation in dpy-10 was isolated from the clk-2(mn159) mutant background, and analysis of the dpy-10 locus (Levy et al 1993) revealed a 3.616-kb deletion and a long 42-bp G/Crich sequence located near one deletion breakpoint (Table 1, Figure 1). Thus, five of six spontaneous mrt-2-induced mutations and one spontaneous clk-2-induced mutation resulted from deletions, three of which displayed G-or G/C-rich sequences near one deletion breakpoint.…”
Section: Resultsmentioning
confidence: 99%